This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: 22 0.9 23 0.9 24 0.9 ...) × × + × + × + × + Let’s denote 1 2 3 21 0.9 22 0.9 23 0.9 24 0.9 ... S = × + × + × + × + Multiple both sides by 0.9 1 2 3 4 0.9 21 0.9 22 0.9 23 0.9 24 0.9 ... S = × + × + × + × + Subtraction the second equation from the first, we get 1 2 3 4 0.1 21 0.9 0.9 0.9 0.9 0.9 ... S = × + + + + + 0.9 21 0.9 30 1 0.9 = × + =Hence (  ) 0.1 30 E N B S = × = (Tips on sum of series: you might practice on computing b n n a S nr = = ∑ , where a, b, r are constants. Think about different situations when r>1, r=1, r<1; what about b is finite or positive infinity? ) See the next page for solutions to problem 2.16, 2.17...
View
Full
Document
This note was uploaded on 04/21/2008 for the course EE 351k taught by Professor Bard during the Fall '07 term at University of Texas.
 Fall '07
 BARD

Click to edit the document details